Family dynamics in the process of feeding of children with cerebral palsy - doi: 10.5020/18061230.2010.p374 - Nadja Maria Vieira Holanda; Izabella Santos Nogueira de Andrade (Universidade de Fortaleza, 2012)
Objective: To understand the family dynamics of children with cerebral palsy during feeding. Methods:  A research with a qualitative approach. The study subjects consisted of ten families of children with cerebral palsy. The children were aged greater than or equal to five years. The data was collected through a semi-structured interview with guiding questions related to the mother-child during feeding, care and difficulties, and mothers' expectations. Discourse analysis was made by means of content analysis technique, comprising the steps of pre-information analysis, exploration of the collected material, processing and interpretation of results.  Results: Family participation during the feeding process of children with cerebral palsy showed to be essential for its efficiency, running continuously in the care and handling of these children, besides highlighting the role of the family, especially the mother figure for feeding and rehabilitation therapy. Conclusion: We conclude that the family has a decisive role in the feeding process, which is vital to promote hydration, weight gain, and minimize the risk of aspiration, which significantly contributes to the quality of life of children with cerebral palsy.